Penerapan Hukuman Kebiri di Indonesia Dalam Perspektif Hukum Islam - Jauhar Nashrullah (Isti`dal : Jurnal Studi Hukum Islam, 2023)
There were pros and cons in various circles regarding the application of additional castration crimes in Indonesia for perpetrators of sexual crimes. This paper will examine the application of castration in Indonesia from the perspective of Islamic legal. This research includes the type of normative juridical research and will use statutory, conceptual, and case approaches. Primary, secondary, and tertiary legal materials collected through library research will later be analyzed qualitatively using prescriptive and descriptive methods. The results of the study concluded that the application of castration in Indonesia is included in the Ta'zir category, so the application of castration in Indonesia is very feasible in Indonesia. Even its application is not arbitrary, because through a strict mechanism and the nature of this punishment is limited to child sexual crimes. This castration is temporary, not permanent. So this application needs to be done to provide a deterrent effect and reduce the risk of recidivism.